Persepsi Siswa SD dalam Penggunaan Strategi Reading Aloud dan Sustained Sailent Reading Terhadap Kemampuan Menjelaskan Isi Bacaan - Fitryatul Irfani; Heriza Dwi Suryani; Adrias Adrias; Nur Azmi Almi (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This article examines the perceptions of upper grade elementary school students towards the use of reading aloud and sustained silent reading strategies in improving the ability to explain the content of reading. This research uses a qualitative approach with descriptive methods. Data collection techniques include: (1) assessment of students' ability to explain the content of reading, (2) interviews with students regarding their perceptions of reading aloud and sustained silent reading strategies, and (3) documentation of the text reading process. The research instruments used were: (1) assessment sheet of the ability to explain the content of reading, (2) structured interview guide, and (3) documentation of students' reading process. The results showed that based on the assessment of the ability to explain the content of reading and interviews regarding the comparison between reading aloud and sustained silent reading strategies, it was concluded that the sustained silent reading strategy was more effective in learning. This is because the strategy makes it easier for students to understand and explain back the content of the reading.